Strain sequence effect on fatigue life and fracture surface topography of 7075-T651 aluminium alloy - Macek, Wojciech (2021)
The paper studies the effect of strain-loading sequence on fatigue lifetime and fracture surface topographies in 7075-T651 aluminum alloy specimens. Fatigue tests were performed in two ways: (i) constant-amplitude loading and (ii) two series of variable amplitude loading with non-zero mean strain values. The topography of the fatigue fractures was measured over their entire surfaces with the help of an optical confocal measurement system. The results of fatigue tests in the form of equivalent strains, εaeq, such as the weighted mean of strain components, εa1, εa2, and fatigue life, Nf, were used as the sum of the partial number of cycles N1, and N2. This study indicates, inter alia, that the values of the fracture surface parameter core height Sk, found in the two-step loading program, are linearly dependent on the equivalent strain, and logarithmically dependent on the fatigue life. © 2021 The Author(s)